Delivery of anti-microRNA-21 by lung-targeted liposomes for pulmonary fibrosis treatment - Lingyue Yan; Yafei Su; Isaac Hsia; Ying Xu; Vui King Vincent-Chong; Wilfrido Mojica; Mukund Seshadri; Ruogang Zhao; Yun Wu (Molecular Therapy: Nucleic Acids, 2023)
Idiopathic pulmonary fibrosis (IPF) is a chronic lung disorder with a low survival rate. Pulmonary fibrosis is one of the complications of COVID-19 and has a high prevalence in COVID-19 patients. Currently, no effective therapies other than lung transplantation are available to cure IPF and post-COVID-19 pulmonary fibrosis. MicroRNAs are small non-coding RNAs that mediate the development and progression of pulmonary fibrosis, thus making them potent drug candidates for this serious disease. MicroRNA-21 (miR-21) promotes not only the differentiation of fibroblasts to myofibroblasts but also epithelial-mesenchymal transition, both of which have been proposed as fundamental processes in pulmonary fibrosis development. Delivery of anti-miR-21 to block the miR-21-associated fibrogenic pathways represents a promising therapy for pulmonary fibrosis. However, microRNA treatment is challenged by quick degradation of RNA in blood, poor cellular uptake, and off-target effects. To overcome these challenges, we developed a lung-targeted, cationic liposome formulation to encapsulate anti-miR-21, enhance its delivery efficiency, and improve the therapeutic efficacy. We optimized the liposome formulation and demonstrated the anti-fibrotic effects using both in vitro and in vivo lung fibrosis models. Our results showed that anti-miR-21 delivered by cationic liposomes suppressed myofibroblast differentiation, reduced the synthesis of extracellular matrix, and inhibited fibrosis progression.